The endogenous erythropoietin in correlation with other erythrocytic parameters in patients with head and neck squamous cell carcinoma treated with platinum-based induction chemotherapy - Leś, Dominika; Saduś-Wojciechowska, Maria; Rutkowski, Tomasz; Wygoda, Andrzej; Składowski, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2019)
Between January 2017 and July 2018 103 patients were included in a prospective study of erythropoietin (EPO) monitoring. The group consisted of 33% patients with oropharynx, 29% with oral cavity, 13% with nasopharynx, 6% with larynx, 6% with hypopharynx, 8% with unknown primary cancer, 4% with nasal cavity, and 1% with salivary gland cancer. Clinic stage: T4 – 50, T3 – 21, T2 – 14, T1 – 10, T0 – 8, and N3 – 19, N2 – 61, N1 – 10, N0 – 13. All patients received from one to four cycles of induction chemotherapy. EPO was measured in blood serum by enzyme-labelled chemiluminescent immunometric assay, using an Immulite 2000XPi analyser before the administration and on day 11 of each chemotherapy cycle. During induction chemotherapy the EPO level was elevated in all patients, which is expressed by means of medians: 10.7 (p = 0.000001) in the middle of cycle 1; 10.9 (p = 0.66) before cycle 2; 14.35 (p = 0.000177) in the middle of cycle 2; 14.95 (p = 0.39) before cycle 3, 17.00 (p = 0.00078) in the middle of cycle 3, and 20.9 after cycle 3 (p = 0.41). The correlation analysis conducted indicates that the administration of one chemotherapy dose results in higher EPO release (two-fold increase in EPO concentration) which intensifies reticulocytes (REC) production but without haemoglobin concentration in reticulocytes (HGB-REC) growth. In consequence, it leads to a decrease in RBC and HGB concentration (29–32 cases). The administration of two and three chemotherapy doses results in the subsequent higher release of EPO, which does not intensify REC production. In consequence, anaemia increases (35 cases).